2014
DOI: 10.1136/postgradmedj-2013-132053
|View full text |Cite
|
Sign up to set email alerts
|

Application of lipoarabinomannan antigen in tuberculosis diagnostics: current evidence

Abstract: Tests based on the detection of mycobacterial lipoarabinomannan (LAM) antigen in urine have emerged as potential point-of-care tests for tuberculosis (TB). We aimed to assimilate the current evidence regarding the diagnostic performance of LAM assays and to ascertain their clinical indication in settings with high and low prevalence of HIV-TB co-infection. Owing to suboptimal sensitivity, the urinary LAM assays are unsuitable as general screening tests for TB. However, unlike traditional diagnostic methods, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Lipoarabinomannan (LAM), a mycobacterial cell wall lipopolysaccharide and virulence factor, has been the most studied TB biomarker due to several attractive features: it is bacterially derived, is abundant in the cell wall of Mycobacterium tuberculosis , is heat and protease stable, and has structural epitopes that are unique to M. tuberculosis . There is extensive evidence that LAM is found in the urine of many TB patients ( 5 , 6 ), and other studies indicate that it may also be found in sputum ( 7 , 8 ) and blood ( 9 , 10 ). While several enzyme-linked immunosorbent assay (ELISA) and rapid (lateral flow) tests have been developed, the only LAM test currently on the market for the clinical diagnosis of TB is the Alere Determine TB LAM test (Alere LF-LAM) from Abbott Diagnostics, a lateral flow test for detecting LAM in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoarabinomannan (LAM), a mycobacterial cell wall lipopolysaccharide and virulence factor, has been the most studied TB biomarker due to several attractive features: it is bacterially derived, is abundant in the cell wall of Mycobacterium tuberculosis , is heat and protease stable, and has structural epitopes that are unique to M. tuberculosis . There is extensive evidence that LAM is found in the urine of many TB patients ( 5 , 6 ), and other studies indicate that it may also be found in sputum ( 7 , 8 ) and blood ( 9 , 10 ). While several enzyme-linked immunosorbent assay (ELISA) and rapid (lateral flow) tests have been developed, the only LAM test currently on the market for the clinical diagnosis of TB is the Alere Determine TB LAM test (Alere LF-LAM) from Abbott Diagnostics, a lateral flow test for detecting LAM in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies on the clinical accuracy of ManLAM for TB diagnosis have reported high clinical specificities ( i.e., the reliability of a test to correctly identify a healthy patient as healthy), but widely varied and often low clinical sensitivities ( i.e., the reliability of a test to correctly identify a sick patient as sick) [37,38]. Along these lines, we recently found that the detectability of ManLAM in human serum significantly improved (∼250×) when analyzing the sample after acidification with perchloric acid (PCA) with an immunoassay as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…12 While poor specificity may reflect the shortcomings of individual assays, it is also possible that false-positive results are due to cross-reactivity with LAM molecules expressed by non-tuberculous mycobacteria (NTM), or related bacteria of the Actinomycetales order. 7,13,14 The LAM antigen has three structural domains: (1) a mannosyl-phosphatidyl-myo-inositol linker, (2) a polysaccharide backbone composed of a D-mannan core and D-arabinan branches, and (3) a capping motif on the terminal ends of the D-arabinan branches. 15 The linker and backbone are conserved in all LAM variants, while the capping motif differs depending on the species of mycobacterium.…”
Section: Introductionmentioning
confidence: 99%